Optimization of Processing Parameters for the Production and Storage of Drum-Dried Jackfruit (Artocarpus Heterophyllus) Powder - Pua, Chun Kiat (2006)
This study concerns with the optimization of formulation and processing parameters of drum-dried jackfruit powder using response surface methodology (RSM). In formulating the jackfruit powder, various concentrations of soy lecithin and gum arabic ranging from 1 to 5% and 5 to 15 %, respectively were tested. The optimum formulation for jackfruit powder contained 2.65% of soy lecithin and 10.28% of gum arabic with 40% v/w water. Soy lecithin and gum arabic significantly (p<0.05) affected the moisture content, bulk density, Hunter L, a, b values and hedonic scores of jackfruit powder with each response following the second-order polynomial model. Optimum processing parameters for drum drying were found when drum clearance of drum dryer was set at 0.01 inch, pool level at 10 cm, and drum rotation speed of 1 to 3 rpm with 3.0 to 4.4 bars of steam pressure. The results showed that the moisture content, water activity, solubility, Hunter L, a, b value, and sensory attributes of jackfruit powder were significantly (p<0.05) influenced by both steam pressure and rotation speed of the drum dryer. The optimum steam pressure and rotation speed of drum dryer were 3.36 bars and 1.2 rpm respectively with predetermined drum clearance of 0.01 inch and 10 cm of pool level. Total colour difference (ΔE), moisture sorption rates and sensory attributes of drum-dried jackfruit powder packaged in aluminum laminated polyethylene (ALP) and metallized co-extruded biaxially oriented polypropylene (BOPP/MCPP) pouches stored at accelerated storage (38oC, with 50, 75 and 90% relative humidity (RH)) were determined over 12 weeks period. The changes in total colour followed zero order reaction kinetics. Packaging materials, storage temperature and RH values significantly (p<0.05) influenced the moisture sorption rates of jackfruit powder. There was a significant (p<0.05) decrease in the intensities of the fruity odour, taste and increase in the lumpiness of the jackfruit powder stored at 38oC with 90% RH. The shelf life of jackfruit powder stored at 38oC and 90% RH was limited by both overall acceptability and the three sensory attributes intensities at week 8 of storage. Jackfruit powder stored at 28oC remained stable and acceptable throughout the storage period for all RH values. The powder packaged in ALP significantly (p<0.05) reduced total colour change, moisture sorption rates, lumpiness intensity of jackfruit powder and was rated higher in terms of overall acceptability over BOPP/MCPP. Results of this study suggested that ALP packaging with storage conditions of 28oC and RH less than 75% was better suited for keeping jackfruit powder.